Some new algorithms of the half-cycle integral algorithm - Wang, M.-L.; Chang, Y (Dianli Xitong Baohu yu Kongzhi, 2009)
Half-cycle integral is based on that the integral of the absolute value of a sinusoidal quantity is a constant in any given half-cycle which is not subjected to the epoch angle of the integral starting point. Usually, it is calculated approximately via trapezoidal rule, then the virtual value. This paper presents the half-cycle integral algorithm and some modifications. Suppose the input signal is sinusoidal, it is analyzed deeply with the replacement of instantaneous value by average value. Instantaneous value can be derived accurately from the average value which renders the modification of the trapezoidal rule and the improvement of precision. Modified Simpson rule is introduced to replace trapezoidal rule.